2016
DOI: 10.1016/j.jecp.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Executive function and magnitude skills in preschool children

Abstract: Executive Function (EF) has been highlighted as a potentially important factor for mathematical understanding. The relation has been well established in school-aged children but has been less explored at younger ages. The current study investigated the relation between EF and mathematics in preschool aged children. Participants were 142 typically developing 3- and 4-year-olds. Controlling for verbal ability, a significant positive correlation was found between EF and general math abilities in this age group. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 60 publications
3
18
0
3
Order By: Relevance
“…The MEFS is nationally normed, has been used with over 30,000 children, and has adequate test-retest reliability (0.86; Carlson, 2017 ). Past studies have established multiple forms of criterion validity for the MEFS (e.g., Doom et al, 2014 ; Fuglestad et al, 2014 ; Hassinger-Das et al, 2014 ; Prager et al, 2016 ). Scores are automatically computed using an algorithm that combines accuracy and response time, and can range from 0 to 100.…”
Section: Methodsmentioning
confidence: 99%
“…The MEFS is nationally normed, has been used with over 30,000 children, and has adequate test-retest reliability (0.86; Carlson, 2017 ). Past studies have established multiple forms of criterion validity for the MEFS (e.g., Doom et al, 2014 ; Fuglestad et al, 2014 ; Hassinger-Das et al, 2014 ; Prager et al, 2016 ). Scores are automatically computed using an algorithm that combines accuracy and response time, and can range from 0 to 100.…”
Section: Methodsmentioning
confidence: 99%
“…The two studies relating a similar neural contrast to math achievement in typically developing young adults and high school students (Gullick, Sprute, & Temple, 2011;Wilkey et al, 2017) found inverse ratio effects correlated with math achievement in bilateral insula, and inferior parietal regions, regions not canonically associated with the processing of numerical information. With the recent array of behavioral data indicating that incongruent trials drive the relation between task performance and mathematics achievement (Bugden & Ansari, 2015;Fuhs & McNeil, 2013;Gilmore et al, 2013;Prager, Sera, & Carlson, 2016), evidence is mounting in favor of the importance of executive function mechanisms and their interaction with magnitude processing mechanisms as a foundation for mathematical competence. The current results lend support to this interpretation in that none of the neural contrasts associated with magnitude processing alone (i.e., balanced for congruency) correlate with mathe- The whole-brain correlation of mathematics achievement with the double-subtraction of the numerical congruency effect minus the flanker congruency effect similarly indicated the importance of attentional components of the task.…”
Section: Relations To Mathematical Competencementioning
confidence: 99%
“…The ability to shift attention between different tasks or information involves the disengagement from an irrelevant task, or from information that becomes no longer relevant, and the subsequent active engagement in a newly relevant task. A specific shifting domain is conceptual shifting, which has been defined as the ability to consciously shift from a concept or a cognitive set to another (Ozonoff et al, 2004); more generally, conceptual shifting can be considered an index of cognitive flexibility (e.g., Miyake et al, 2000;Prager, Sera, & Carlson, 2016). One of the most widely used tools to assess conceptual shifting is the Wisconsin Card Sorting Test (WCST, Berg, 1948) and its modified version for children (MCST;Nelson, 1986).…”
Section: Introductionmentioning
confidence: 99%